Two-Coil Receiver for Electrical Vehicles in Dynamic Wireless Power Transfer - Tommaso Campi; Silvano Cruciani; Francesca Maradei; Mauro Feliziani (Energies, 2021)
Dynamic wireless power transfer (DWPT) of electric vehicles (EVs) is the future of urban mobility. The DWPT is often based on a series of short track pads embedded in road pavement that wirelessly transfers electrical energy to EVs equipped with a pickup coil for battery charging. An open problem with this technology is the variation of the coupling factor as a vehicle switches from one transmitting coil to another during its motion. This can cause a significant change in power with possible power spikes and holes. In order to overcome these issues, a new architecture is here proposed based on two pick-up coils mounted in the vehicle underneath. These identical receiver coils are placed in different positions under the vehicle (one in front and the other in the rear) and are activated one at a time so that inductive coupling is always good enough. This innovative configuration has two main advantages: (i) it maintains a nearly constant coupling factor, as well as efficiency and transferred power, as the vehicle moves along the electrified road; (ii) it significantly reduces the cost of road infrastructure. An application is presented to verify the proposed two-coil architecture in comparison with the traditional one-coil. The results of the investigation show the significant improvement achieved in terms of maximum power variation which is nearly stable with the proposed two-coil architecture (only 2.8% variation) while there are many power holes with the traditional single coil architecture. In addition, the number of the required transmitting coils is significantly reduced due to a larger separation between adjacent coils.